SIKAP DAN POTENSI KETERLIBATAN MASYARAKAT DALAM PENGELOLAAN KEBUN RAYA KUNINGAN - , ANDREE INDIRA RYENALDY; , Kristiani Fajar Wianti, S.Hut, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kuningan botanical garden is a green space which is still developed in Padabenghar village, kuningan regency. The developing of Kuningan botanical garden caused impact to the social and economic condition which would bring responses from the society against the devolepment and also a potential of the society getting involved in managing Kuningan botanical garden. This research was conducted using questionnaire method to indentify the society responses and aspiration to identify the potential of the society involvement in managing Kuningan botanical garden. The questionnaire consists of questions about planning, developing process, and managing. Whereas the aspiration consists of questions about types of involvement that the society wants in managing Kuningan botanical garden. From the analyzing result using descriptive statistic shows that most of the society in Padabenghar village showing supporting respond (Category 2) against the developing of Kuningan botanical garden with much support responds records. Nearly 93% of the society wants to be involve in managing Kuningan botanical garden in such a way that a partisipative management was needed to accommodate what the society wants and also to change the society paradigm against the development of Kuningan botanical garden so that it would give strong support in the process of developing and managing Kuningan botanical garden.